From Local Wisdom To Cultural Branding: Visual Communication And Identity Construction In Rural Bamboo Communities - Tanzila Vibia Mumtaza; Didit Widiatmoko Suwardikun; Syarif Hidayat (KOMUNIKA, 2026)
This study examines how visual communication constructs collective identity through thetranslation of local wisdom into cultural branding strategies in rural bamboo handicrafts.Focusing on Muaradua village, Sukabumi, Indonesia, the study reconceptualizes branding notas a promotional technique but as a process of symbolic identity construction. Employing aqualitative case study combined with a research-based design approach, data were collectedfrom senior artisans, small enterprise managers, and local facilitators through observations,in-depth interviews, focus group discussions, and visual documentation. The findings indicatethat weak cultural positioning is primarily due to the absence of a structured, collectivelygoverned visual identity system rather than to limitations in production capacity or marketaccess. Local artistic wisdom remains fragmented because it has not been institutionalizedwithin a structured framework of visual governance. This study proposes visual brandguidelines as a mechanism of visual governance that translates cultural values into a coherentidentity system capable of stabilizing meaning across actors and media. The primarycontribution of this study lies in demonstrating how visual communication functions as aprocess of identity construction in rural creative enterprises and how collective visual systemsoperate as symbolic infrastructure in cultural branding. These findings contribute to culturalbranding theory and visual communication studies by repositioning branding as an institutionaland symbolic process rather than a short-term promotional strategy.